2004
DOI: 10.1242/dev.01324
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ superfamily signals are required for morphogenesis of the kidney mesenchyme progenitor population

Abstract: The TGFβ superfamily plays diverse and essential roles in kidney development. Gdf11 and Bmp4 are essential for outgrowth and positioning of the ureteric bud, the inducer of metanephric mesenchyme. During nephrogenesis, Bmp7 is required for renewal of the mesenchyme progenitor population. Additionally, in vitro studies demonstrate inhibitory effects of BMPs and TGFβs on collecting duct branching and growth. Here,we explore the predicted models of TGFβ superfamily function by cell-specific inactivation of Smad4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 44 publications
5
100
1
Order By: Relevance
“…Inactivation of cMyc in early metanephric mesenchyme (e11.5) (59) showed that c-Myc plays an early and crucial role in the renal cap mesenchymal cells. Ablation of c-Myc resulted in depletion of the renal stem/progenitor cell population caused by a major decrease in proliferation that likely impaired their self-renewal potential (2).…”
Section: Role Of C-myc In Kidney Development and Homeostasismentioning
confidence: 99%
“…Inactivation of cMyc in early metanephric mesenchyme (e11.5) (59) showed that c-Myc plays an early and crucial role in the renal cap mesenchymal cells. Ablation of c-Myc resulted in depletion of the renal stem/progenitor cell population caused by a major decrease in proliferation that likely impaired their self-renewal potential (2).…”
Section: Role Of C-myc In Kidney Development and Homeostasismentioning
confidence: 99%
“…All UB cells originate from the WD. (70) However, soon after the UB emerges it becomes divided into distinct tip and trunk domains. In addition to Ret and Gfra1, there are many other genes expressed specifically in the tip domain but not in the trunks, including Wnt11, Crlf1, and CXCL14 to name a few; (71,72) conversely, different genes are expressed only in the trunks (e.g.…”
Section: The Role Of Localized Gdnf/ret Signaling In Ureter Formationmentioning
confidence: 99%
“…Whole mount and non-radioactive section in situ hybridizations were performed as previously described (Oxburgh et al, 2004).…”
Section: In Situ Hybridizationmentioning
confidence: 99%